Kontrol Kecepatan Motor Penggerak Feeder Pada Mesin Pencacah Jerami Untuk Sistem Reaktor Biogas Berbahan Baku Jerami - Kartika - -; Roswaldi Sk -; Amril - -; Sandra - - (Jurnal Ilmiah Poli Rekayasa, 2017)
The production of one ton of rice straw will produce 250 kg of dry hay (Isni, 2011). A sizeable amount, straw as one of the ingredients that are very effectively used as raw material for biogas. Straw into biogas conversion value reaches 250-350 liter / kg dry weight (Arati, 2009). For a perfect straw metabolism, staw should be cut first. Enumeration is done manually is less efficient because the enumeration is done by using a knife to cut hay will produce a piece of straw that are not uniform. Good hay cutting measure is about 2-5 cm. If the straw enumeration is done by machine, then it takes the feeder to the cutting machine tool that can feed the straw so that the resulting size of 2-5 cm. To make the necessary feeder, conveyor, DC motors, magnetic clutch and infrared sensors. Conveyor serves as a carrier of straw, DC motors as actuators, magnetic clutch as conveyor control and infrared sensor as a measure of pieces of straw. After testing, show that it works and works well.